PENGARUH KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI HARGA DAN KUALITAS PELAYANAN TERHADAP REPEAT BUYING (Studi Pada Pelanggan Barbershop di Kota Malang) - Achmad Zaini; Diana Eka Poernamawati (Adbis: Jurnal Administrasi dan Bisnis, 2019)
This study aims to analyze the variables of price and quality of customer in influencing repeat buying both directly and indirectly through variable of customer satisfaction. The analytical tool used in this study is Partial Least Square (PLS) analysis. The results showed several findings that were consistent with previous studies. The price variable has a significant positive effect on Barbershop customer satisfaction The service quality variable has a significant positive effect on customer satisfaction Variable customer satisfaction has a significant effect on repeat buying Price variable has no significant effect on repeat buying. Price variable has a significant positive effect on repeat buying through customer satisfaction variables The customer satisfaction variable is a full mediator. Service quality variable has a significant positive effect on repeat buying Service quality variable has a significant positive effect on repeat buying through customer satisfaction variables Variable customer satisfaction is a partial mediator. The relationship between the variables involved are: price, service quality, customer satisfaction and repeat buying of 89.56%,